Quimiodiversidade e bioatividade do óleo essencial e extrato de folhas de Genipa americana L. a Aceria guerreronis (Acari: Eriophyidae) - Jesus, Alex Souza de (2019)
The jenipapo tree Genipa americana L. (Rubiaceae) is a fruit-bearing species native to Brazil, with bioactive compounds such as tannins, mannitol, methyl esters, and iridoids. Aceria guerreronis (Acari: Eriophyidae) is a key pest of the coconut (Cocos nucifera L.) crop, in which Brazil has a prominent role in world production. The objective of this study was to identify the chemical composition of the essential oil and the methanolic extract of G. americana leaves and evaluate their acaricidal activity against the coconut mite. The essential oil was obtained from fresh leaves collected at Embrapa Coastal Tablelands Germplasm Active Bank of Jenipapo through hydrodistillation. To obtain the methanolic extract, fresh leaves were macerated in methanol for 48 hours and the extract was filtered and concentrated in a rotary evaporator. The qualitative and quantitative chemical composition of the essential oil was analyzed by gas chromatography, with flame ionization detector (FID), coupled to mass spectrometry (GC-MS). For concentration-mortality bioassays, adults of coconut mite were subjected to increasing concentrations of G. americana essential oil and methanolic extract. In addition to the toxicity evaluation, repellency was evaluated by releasing mites in the center of an arena with half the area sprayed and the other half unsprayed. The major compounds identified in the essential oil of young mature leaves were: naphthalene, (E)-β-ocimene, (2E)-decenal, (2E, 4E)-decadienal, (E)-cariophylene, (E)-β-ionone, (E, E)-α-farnesene, hexyl benzoate, pentadecanal, and linoleic acid. There was strong oxidation of fatty acids, aldehydes, and terpenes at the extraction times evaluated, indicating the presence of oxidase. In the young leaves, there was a predominance of monoterpenes, sesquiterpenes, aldehydes, and fatty acids. In the mature leaves, the same compounds were present, including some diterpenes, suggesting the expression of diterpene synthase during leaf senescence. The bioassays revealed strong acaricidal activity of essential oil (LC50 = 0.41 mg mL-1, LC90 = 6.43 mg mL-1) and methanolic extract (LC50 = 0.60 mg mL-1 and LC90 = 16.69 mg mL -1) against the coconut mite. The estimated values of LC50 and LC90 repelled the coconut mite 24 hours after application, with a higher percentage of repellency for essential oil. The methanolic extract exhibited low persistence in reference to the coconut mite, with acaricidal activity concentrated in the first 42 hours. Compounds of the essential oil and the methanolic extract of jenipapo tree leaves have potential for assisting in control of coconut mite in coconut plantations.